Pengaruh Pelatihan dan Kompetensi Terhadap Peningkatan Produktivitas Melalui Motivasi Ekstrinsik di PT Jayaindo Abadi Makmur (Cikarang) - Marshela, Prolice Anggraeni; Prasilowati, Sri Lestari (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to analyze how much influence training and competence have on increasing productivity through extrinsic motivation. In this study, the population as well as the sample were employees of PT Jayaindo Abadi Makmur, namely 33 people with a saturated sample method. Analysis using SPSS. The results of the research conducted competence positively and significantly affects extrinsi motivation. Competence positively and significantly affects productivity.